3.ACUTE AND SUBACUTE TOXICITY OF CHLOROFORM EXTRACT OF XANTHIUM STRUMARIUM LEAVES (Iraqi Journal of Medical Sciences, 2019)
Background:The incidence of cancer is increasing worldwide. Xanthium strumarium may possess anticancer activity, the plant extract for in vitro anticancer activity against a panel of three human cell lines (Breast MCF7, Renal TK10 and Melanoma UACC62), exhibit anticancer activity against these three human cell lines screened by National Cancer Institute.Objective:To investigate the safety of chloroform extract of Xanthium strumarium leaves, which showed potent cytotoxic activity against tumor cells.Methods:The leaves were dried and grounded into fine powder, and extracted with chloroform, that showed potent cytotoxic activity has been tested against two animal species mice and rats for testing its safety. Toxicity was evaluated in Swiss albino mice by feeding with serial doses of extract between 1.0 to 20.0 gm/kg orally and observed continuously for the first 4 hr and hourly for the next 24 hr, then every 6 hr for 48 hr (72 hr, acute toxicity). Rats were also fed with extract single dose of 5 gm/kg, the toxicity was carried out by assessing the effects on biochemical parameters, body weight and relative organ weights for both male and female rats.Results:LD50 of chloroform extract was 3.07 gm/kg. The biochemical finding showed no significant differences compared to control. No significant weight changes occur throughout the study.Conclusion:Chloroform extract has low LD50 (3.07 gm/kg), but the acute toxicity study showed no mortality or signs of toxicity, with non-significant changes in body weights, relative organ weights, and biochemical tests among treated groups compared to their controls.Keywords:Xanthium strumarium, chloroform extract, cytotoxic herb, acute toxicityCitation:Alsabah AS, Abd AH, Al-Shammari AM. Acute and subacute toxicity of chloroform extract of Xanthium strumarium leaves. Iraqi JMS. 2019; 17(2): 108-113. doi: 10.22578/IJMS.17.2.3
Keywords: Xanthium strumarium; chloroform extract; cytotoxic herb; acute toxicity